WAGNER - MYTH AND IMAGINATION IN TOTAL ART - Castro, Paulo Alexandre (Cadernos de Educação Tecnologia e Sociedade, 2020)
The purpose of this brief essay is to outline what can be considered the combination of two essential elements in the realization of Wagner's works: the strength of the myth's plot and the imaginative process in the creation of the artwork. However, it is not a simple presentation of these elements, but how Wagner, when wishing to create the total work of art, is guided by a phenomenological thought.